The Impact of Digital Supply Chain on Sustainable Performance: The Moderating Role of Big Data Analytics Capabilities - Lemoun, Amro Adel Abu; Dellagi, Hatem; Mohammad, Suleiman Ibrahim Shelash; Al Oraini, Badrea; Vasudevan, Asokan; Hunitie, Mohammad Faleh Ahmmad (Journal of Posthumanism, 2025)
Amidst a period characterized by the restructuring of global supply chains via digitalization, its implications on sustainability have become a necessity, especially in developing economies. This research investigates the contribution of the digital supply chain to sustainable performance, with big data analytics capacity as a moderating factor, in the Jordanian industrial sector. Based on a comprehensive dataset collected from 308 managers spanning various industrial sectors, the research offers empirical evidence on how digitalization reshapes industrial sustainability. The results indicate that the overall level of digital supply chain adoption in Jordanian industries is moderate. Similarly, big data analytics capability revealed a positive significant effect on sustainable performance, with human capability being the most essential. Nevertheless, the moderating effect of big data analytics capability was selective; it effectively improved the connection between digital logistics and sustainable performance, but did not have any notable effect on digital suppliers or digital manufacturing. This study gives a holistic model for industrial companies to deal with the dynamics of contemporary supply chains by incorporating digital transformation, big data, and sustainability, thereby resulting in environmental, social, and economic sustainability in the long run.